Islamic Legal Perspectives on Gender Equality and Human Rights: Contributions to the 2030 Sustainable Development Goals - Muktamar Ibrahim; Imron Hadi (WISE Pendidikan Indonesia, 2026)
This study aims to analyze Islamic legal perspectives on gender issues and human rights in contemporary society and to examine their contribution to the achievement of the Sustainable Development Goals (SDGs) 2030, particularly Goal 5 on gender equality and Goal 16 on peace, justice, and strong institutions. This study employed a qualitative library research design using secondary data from academic books, peer-reviewed journal articles, Qur’anic exegesis, legal documents, and scholarly publications related to Islamic law, gender equality, human rights, and sustainable development. The data were collected through documentation techniques and analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that Islamic law normatively upholds justice (al-‘adl), equality (al-musāwah), human dignity (karāmah al-insān), and public welfare (maṣlaḥah), which are compatible with contemporary human rights and SDG principles. However, its implementation remains challenged by patriarchal culture, conservative interpretations, and weak institutional translation into gender-responsive policies. This study contributes by positioning Islamic law as a contextual, maqāṣid-oriented, and policy-relevant ethical framework for advancing gender equality, human rights protection, and sustainable social development.